Desain Berpikir: Pengaruh Penggunaan Model Pengajaran Berbasis Pemecahan Masalah Pada Pendidikan Inklusif - Fadhila Eka Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Problem solving is a process that involves mental operations such as deduction, induction, classification, evaluation, and reasoning. This study aims to capture the landscape of problem solving research, particularly in secondary schools. The method used is bibliometric descriptive analysis. The source of the data obtained came from the Scopus database. 100 relevant documents were found, indicating the increasing but still limited interest of researchers in problem-solving skills in inclusive education. This research aims to direct future research and support the development of responsive and inclusive education policies.